The Effectiveness of Group Counseling by Using Cognitive Behavioral Therapy Approach with Cinematherapy and Self-talk Techniques to Reduce Social Anxiety at SMK N 2 Semarang (Jurnal Bimbingan Konseling, 2018)
The purpose of this study was to investigate the effectiveness of the implementation of groups counseling services with cognitive behavior therapy (CBT) approach using cinematherapy and self-talk techniques in reducing students' social anxiety. This study used a Repeated Measure Design as the experimental contrivance. The participants used in this study were 14 students in SMK N 2 Semarang. The selection of the subjects is using purposive sampling technique that is based on social anxiety criteria obtained from the results of social anxiety scale scores. Social Anxiety Scale for Adolescents is the instruments used in this study. Data analysis techniques were used is the Sphericity and ANOVA tests. The results of the study showed that the group counseling with cognitive behavior therapy (CBT) approach by using cinematherapy and self-talk techniques were effective in reducing students' social anxiety. The findings of this study prove the effectiveness of group counseling services in the cognitive behavior therapy (CBT) approach using cinematherapy and self-talk techniques for the students in Semarang city, Indonesia.